Langue pure et lalangue : rencontres entre Benjamin et Lacan - Oliveira, Clàudio (Filozofski vestnik, 2019)
The aim of this article is to open an approach – an initiative still rare in the philosophical and psychoanalytic fields – between the thought of Jacques Lacan and the Frankfurt School, focusing on the discussion on the conceptions of language and idiom present in Walter Benjamin’s and Lacan’s works. In doing so, the author will be guided by Agamben’s reading of Benjamin, a reading that emphasises the idea of the origin of the historical condition of man as coinciding with and being inseparable from the emergence of signification in human language. Starting from this elaboration, it will be possible to think with Benjamin about another language, which he sometimes presents as something coming before history and language’s fall into the realm of signification, and sometimes as something coming after history – and through this, the idea of a “pure language”. Would it be possible, then, to draw a parallel between such “pure language” as elaborated by Benjamin, and the conception of “letter” in Lacan’s thought? Such is the path opened up by this text.